Slanting the light - Marais, Shirley (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
Through my poetry I attempt to make sense of my encounters with myself by bringing to creative expression my experiences of and felt responses to people, places and situations. Among the poets who have had a significant influence on my work are Robert Berold, for his quiet assertion of intense, dramatic images; Frank O'Hara for his disciplined sense of mischief; Joan Metelerkamp for her meticulous attention to form and the way she makes a poem breathe; Robert Creeley for his ability to create free-floating meaning; and Mangaliso Buzani, for his fierce, honest poetics.
Keywords: South African poetry (English) -- 21st century; Creative writing (Higher education) -- South Africa